The effects of increased endurance training load on biomarkers of heat intolerance during intense exercise in the heat - Lim, C. L.; Pyne, D.; Horn, P.; Kalz, A.; Saunders, P.; Peake, J.; Suzuki, K.; Wilson, G.; Mackinnon, L. T. (Applied Physiology, Nutrition, and Metabolism, 2009)
The effects of increased training (IT) load on plasma concentrations of lipopolysaccharides (LPS), proinflammatory cytokines, and anti-LPS antibodies during exercise in the heat were investigated in 18 male runners, who performed 14 days of normal training (NT) or 14 days of 20% IT load in 2 equal groups. Before (trial 1) and after (trial 2) the training intervention, all subjects ran at 70% maximum oxygen uptake on a treadmill under hot (35 °C) and humid (~40%) conditions, until core temperature reached 39.5 °C or volitional exhaustion. Venous blood samples were drawn before, after, and 1.5 h after exercise. Plasma LPS concentration after exercise increased by 71% (trial 1, p < 0.05) and 21% (trial 2) in the NT group and by 92% (trial 1, p < 0.01) and 199% (trial 2, p < 0.01) in the IT group. Postintervention plasma LPS concentration was 35% lower before exercise (p < 0.05) and 47% lower during recovery (p < 0.01) in the IT than in the NT group. Anti-LPS IgM concentration during recovery was 35% lower in the IT than in the NT group (p < 0.05). Plasma interleukin (IL)-6 and tumor necrosis factor (TNF)-a concentrations after exercise (IL-6, 3-7 times, p < 0.01, and TNF-a, 33%, p < 0.01) and during recovery (IL-6, 2-4 times, p < 0.05, and TNF-a, 30%, p < 0.01) were higher than at rest within each group. These data suggest that a short-term tolerable increase in training load may protect against developing endotoxemia during exercise in the heat.